2017
DOI: 10.2217/rme-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Cells Expressing Markers of Female Germ Cells from Premature Ovarian Failure Patient-Specific Induced Pluripotent Stem Cells

Abstract: Our in vitro system was beneficial for POF-iPSCs differentiated cells to express STELLA, VASA and SCP3, which were the markers of meiosis initiation of FGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Mouka et al generated iPSCs by transducing erythroblasts, which were derived from peripheral blood mononuclear cells purified from patients with azoospermia, with Sendai viruses expressing the four mentioned factors 7 . It has also been reported that specific iPSCs of patients with POF successfully expressed female germ cell markers 120 . The patient-specific iPSCs achieved the ability to differentiate into three germ layers with pluripotency, which provides a potential method for repairing spermatogenesis and oogenesis in patients with complex chromosomal rearrangements.…”
Section: Application Of Stem Cell Therapies In Infertilitymentioning
confidence: 92%
“…Mouka et al generated iPSCs by transducing erythroblasts, which were derived from peripheral blood mononuclear cells purified from patients with azoospermia, with Sendai viruses expressing the four mentioned factors 7 . It has also been reported that specific iPSCs of patients with POF successfully expressed female germ cell markers 120 . The patient-specific iPSCs achieved the ability to differentiate into three germ layers with pluripotency, which provides a potential method for repairing spermatogenesis and oogenesis in patients with complex chromosomal rearrangements.…”
Section: Application Of Stem Cell Therapies In Infertilitymentioning
confidence: 92%